Gold‐Catalyzed Post‐Ugi Cascade Transformation for the Synthesis of 2‐Pyridones. Issue 14 (2nd April 2019) - Du, Xiaochen; Yu, Jiafeng; Gong, Jing; Zaman, Manzoor; Pereshivko, Olga P.; Peshkov, Vsevolod A.
Abstract : A gold‐catalyzed post‐Ugi cascade transformation for the synthesis of 2‐pyridones is described. The process involves furan–alkyne cyclization followed by furan ring‐opening and cleavage of the isocyanide‐originated fragment. The initially formed cis double bond can isomerize into a more stable trans double bond upon prolonged exposure to a strong Brønsted acid. Thus, the overall strategy provides a viable access towards two types of 2‐pyridones. Abstract : A gold‐catalyzed post‐Ugi cascade transformation for the synthesis of two types of 2‐pyridones is described. The process involves furan–alkyne cyclization followed by a furan ring‐opening and a cleavage of the isocyanide‐originated fragment.